Microbiota-mediated skewing of tryptophan catabolism modulates CD4+ T cells in lupus-prone mice - Josephine Brown; Georges Abboud; Longhuan Ma; Seung-Chul Choi; Nathalie Kanda; Leilani Zeumer-Spataro; Jean Lee; Weidan Peng; Joy Cagmat; Tamas Faludi; Mansour Mohamadzadeh; Timothy Garrett; et al. (iScience, 2022)
Summary: A skewed tryptophan metabolism has been reported in patients with lupus. Here, we investigated the mechanisms by which it occurs in lupus-susceptible mice, and how tryptophan metabolites exacerbate T cell activation. Metabolomic analyses demonstrated that tryptophan is differentially catabolized in lupus mice compared to controls and that the microbiota played a role in this skewing. There was no evidence for differential expression of tryptophan catabolic enzymes in lupus mice, further supporting a major contribution of the microbiota to skewing. However, isolated lupus T cells processed tryptophan differently, suggesting a contribution of T cell intrinsic factors. Functionally, tryptophan and its microbial product tryptamine increased T cell metabolism and mTOR activation, while kynurenine promoted interferon gamma production, all of which have been associated with lupus. These results showed that a combination of microbial and T cell intrinsic factors promotes the production of tryptophan metabolites that enhance inflammatory phenotypes in lupus T cells.